2017
DOI: 10.18632/oncotarget.17491
|View full text |Cite
|
Sign up to set email alerts
|

The value of diffusion kurtosis imaging in assessing pathological complete response to neoadjuvant chemoradiation therapy in rectal cancer: a comparison with conventional diffusion-weighted imaging

Abstract: ObjectivesThe aim of this study is to comprehensively evaluate the advantage of diffusion kurtosis imaging (DKI) in distinguishing pathological complete response (pCR) from non-pCR patients with locally advanced rectal cancer (LARC) after neoadjuvant chemoradiation therapy (CRT) in comparison to conventional diffusion-weighted imaging (DWI).Material and MethodsFifty-six consecutive patients diagnosed with LARC were prospectively enrolled and underwent pre- and post-CRT MRI on a 3.0 T MRI scanner. Apparent diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 43 publications
(41 reference statements)
0
48
1
Order By: Relevance
“…In addition, this study found that pre‐ADC and pre‐D values significantly increased in the pCR group compared with post‐ADC and post‐D values. It was different from several previous studies that obtained increased ADC values in the pCR and non‐pCR groups . Furthermore, several studies showed that posttreatment ADC and D values could help distinguish pCR from non‐pCR in patients with LARC.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…In addition, this study found that pre‐ADC and pre‐D values significantly increased in the pCR group compared with post‐ADC and post‐D values. It was different from several previous studies that obtained increased ADC values in the pCR and non‐pCR groups . Furthermore, several studies showed that posttreatment ADC and D values could help distinguish pCR from non‐pCR in patients with LARC.…”
Section: Discussioncontrasting
confidence: 93%
“…Perhaps the necrotic area in the tumor could decrease the movement of water molecules and also inhibit the delivery of therapy due to lack of vascularization. Conversely, several studies reported that pretreatment ADC and D values were not associated with the pCR status. These differences might be because of the variations in the MRI technique and the difference in measurement methodology such as ROI selection.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations